2007
DOI: 10.1074/jbc.m609983200
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Balance between Caldesmon Regulated by p21-activated Kinases and the Arp2/3 Complex Govern Podosome Formation

Abstract: Podosomes are dynamic cell adhesion structures that degrade the extracellular matrix, permitting extracellular matrix remodeling. Accumulating evidence suggests that actin and its associated proteins play a crucial role in podosome dynamics. Caldesmon is localized to the podosomes, and its expression is down-regulated in transformed and cancer cells. Here we studied the regulatory mode of caldesmon in podosome formation in Rous sarcoma virus-transformed fibroblasts. Exogenous expression analyses revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 51 publications
4
51
0
2
Order By: Relevance
“…We recently reported that CaD negatively regulates the formation of invadopodia/podosomes, which are dynamic cell adhesion structures involved in cancer cell invasion (37). The forced expression of CaD inhibits invadopodium/podosome formation, leading to suppression of the invasive activity of cancer cells (63).…”
Section: Gc-induced Up-regulation Of Caldesmon Expression Suppresses mentioning
confidence: 99%
“…We recently reported that CaD negatively regulates the formation of invadopodia/podosomes, which are dynamic cell adhesion structures involved in cancer cell invasion (37). The forced expression of CaD inhibits invadopodium/podosome formation, leading to suppression of the invasive activity of cancer cells (63).…”
Section: Gc-induced Up-regulation Of Caldesmon Expression Suppresses mentioning
confidence: 99%
“…Low-molecularmass isoforms of caldesmon (l-caldesmon, 70 to 80 kDa) are thought to be widely distributed in nonmuscle tissues, but only a few studies have used immunohistochemistry to investigate the distribution of caldesmon in selected tissues Fujita et al 1984;Ishimura et al 1984). l-Caldesmon has a role in the organization and stabilization of the microfilament network, thus regulating proliferation and migration (Kordowska et al 2006;Yokouchi et al 2006;Morita et al 2007). High-molecular-mass isoforms (h-caldesmon, 120 to 150 kDa) are predominantly expressed in differentiated smooth-muscle cells (SMCs), with only a few reported exceptions; platelets, colorectal pericryptal fibroblasts, and myoepithelial cells of galactophorous sinuses of human breast tissue contain h-caldesmon as well (Kakiuchi et al 1983;Frid et al 1992;Lazard et al 1993;Nakayama et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It turned out that the formation of podosomes was more tightly correlated with PAK-mediated phosphorylation of CaD. 187 It was suggested that PAK phosphorylation renders CaD more effective in displacing Arp2/3 115 and thereby increases its ability to inhibit podosome formation. Such an effect should be readily testable by biochemical experiments.…”
Section: Phosphorylation As a Regulatory Mechanismmentioning
confidence: 99%